KEPEMIMPINAN PENDIDIKAN BERBASIS NILAI DALAM MENGHADAPI TANTANGAN ABAD KE-21 - Elin Yufriyani; Kartika Solihat; Fuad Abdul Baqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational leadership in the 21st century faces increasingly complex challenges driven by rapid technological advancement, social change, and moral issues in educational practices. These conditions require educational leaders to not only possess managerial competence but also strong value-based leadership. This study aims to examine value-based educational leadership in addressing the challenges of 21st-century education in the Indonesian context. The study employs a systematic literature-based approach by analyzing national scholarly publications published between 2021 and 2025 that discuss educational leadership, values, and contemporary educational challenges. The findings indicate that value-based educational leadership plays a strategic role in shaping positive organizational behavior, strengthening school culture, enhancing teachers’ professional commitment, and supporting ethical and humanistic educational transformation. Value-based leadership serves as a moral compass that guides educational leaders in managing change while maintaining the core purpose of education. This study highlights the importance of integrating values into educational leadership as a sustainable strategy to improve school quality and educational outcomes in the 21st century. Keywords: educational leadership, value-based leadership, 21st-century education, school leadership, organizational behavior